The Role of the Community Guidance Unit in Preventing Fraud Crimes in the Legal Jurisdiction of Garut Police Station - Jalal, M. Yusuf Andi (Advances in Police Science Research Journal, 2024)
The role of Indonesia Police in this case the Satbinmas Garut Police which relation and direct communication with community to expected have the important role in preventif of crime, such as the fraud which the first rank of criminal crime in Garut Polres. This research aims to know the role of the Satbinmas in efforts to prevent fraud criminal crime in Garut Police jurisdiction and explained the factors which appointment of the role of the Satbinmas in efforts to prevent fraud criminal crime in Garut Police jurisdiction. The research applied in Garut Polres with descriptive qualitative approach of research. The informans consist of Head of Garut Police, Head of Satbinmas Garut Polres and community as participant. The gathered of data used of observation, interview and documentation. Data analysis in qualitative consist of reduction, preparation, verification and take of conclusion. The result of research found that the role of the Satbinmas in efforts to prevent fraud criminal crime in Garut Police jurisdiction with applied of data collection, counceling and coaching have effective in minimalization of fraud criminal crime in Garut Polres jurisdiction. The determinants factors which applied of the role of the Satbinmas in efforts to prevent fraud criminal crime in Garut Police jurisdiction consist of law enforcement, public awareness and infrastructure. For that required of added the personnel of Satbinmas, so the available of member can to width of the move from Satbinmas Garut Police. To handling of socialization the counceling about the fraud criminal crime and added of fund for accomodation and transportation and improvement of infrastructure of Satbinmas which make it easy of personnel mobility in applied of data collection, counceling and direction to community.